Are TKAs Performed in High‐volume Hospitals Less Likely to Undergo Revision Than TKAs Performed in Low‐volume Hospitals?. Issue 11 (November 2017) - Jeschke, Elke; Citak, Mustafa; Günster, Christian; Halder, Andreas Matthias; Heller, Karl‐Dieter; Malzahn, Jürgen; Niethard, Fritz Uwe; Schräder, Peter; Zacher, Josef; Gehrke, Thorsten
Abstract: Background: High‐volume hospitals have achieved better outcomes for THAs and unicompartmental knee arthroplasties (UKAs). However, few studies have analyzed implant survival after primary TKA in high‐volume centers. Questions/Purposes: Is the risk of revision surgery higher when receiving a TKA in a low‐volume hospital than in a high‐volume hospital? Methods: Using nationwide billing data of the largest German healthcare insurer for inpatient hospital treatment, we identified 45, 165 TKAs in 44, 465 patients insured by Allgemeine Ortskrankenkasse who had undergone knee replacement surgery between January 2012 and December 2012. Revision rates were calculated at 1 and 2 years in all knees. The hospital volume was calculated using volume quintiles of the number of all knee arthroplasties performed in each center. We used multiple logistic regression to model the odds of revision surgery as a function of hospital volume. Age, sex, 31 comorbidities, and variables for socioeconomic status were included as independent variables in the model. Results: After controlling for socioeconomic factors, patient age, sex, and comorbidities, we found that having surgery in a high‐volume hospital was associated with a decreased risk of having revision TKA within 2 years of the index procedure. The odds ratio for the 2‐year revision was 1.6 (95% CI, 1.4‐2.0; p < 0.001) for an annual hospital volume of 56 or fewer cases, 1.5 (95% CI, 1.3‐1.7; p < 0.001) for 57 to 93 cases, 1.2 (95% CI, 1.0‐1.3; p = 0.039) for 94 to 144 cases, and 1.1 (95% CI, 0.9‐1.2; p = 0.319) for 145 to 251 cases compared with a hospital volume of 252 or more cases. Conclusions: We found a clear association of higher risk for revision surgery when undergoing a TKA in a hospital where less than 145 arthroplasties per year were performed. The study results could help practitioners to guide potential patients in hospitals that perform more TKAs to reduce the overall revision and complication rates. Furthermore, this study underscores the importance of a minimum hospital threshold of arthroplasty cases per year to get permission to perform an arthroplasty. Level of Evidence: Level III, therapeutic study.